AIDS Prevention Strategies in a High-Risk Population - Sakondhavat, Chuanchom; Borkum, Arawan; Chaichanavong, Sirichai; Sakammai, Soontorn; Pinitsoontorn, Pattamavadee (Srinagarind Medical Journal, 2013)
Although Acquired Immune Deficiency Syndrome is not yet epidemic in Thailand , there is evidence that AIDS is spreading to Asia. Because the disease is most likely to first establish itself among high risk group it is important to develop educational programs to promote accurate knowledge of AIDS and preventive health behavior.This study will test three education strategies among high a risk group to develop cost-effective AIDS-prevention education. The study will be of benefit to others who are interested in AIDS education strategies.